An analysis of current literature courses, teaching and learning approaches to foster 21st century student generation´s motivation for the bachelor of arts in English Teaching major at the University of El Salvador main campus, semester II, 2012. - Mendoza López, Laura de Jesús
The research study “An analysis of Current Literature Courses, Teaching and Learning Approaches to Foster 21st Century Student Generation´s Motivation for the Bachelor of Arts in English Teaching Major at the University of El Salvador Main Campus, Semester II, 2012” was carried out to identify the teaching and learning approach of English Literature. This study identifies various factors that may help the teaching of teaching English Literature and help students enjoy both courses with the application of 21st century teaching educational tools. This undergraduate research work was aimed to implement different ICTs based- learning activities such as Blogs, Facebook, Wikis , to ascertain if they help the students to be actively involved in English Literature classes.